SP2.1.7Navigating surgical training: a game of trust. (28th October 2021) - Shah, Adarsh P; Walker, Kim; Hawick, Lorraine; Walker, Kenneth G; Cleland, Jennifer
Abstract: Introduction: One premise of the Improved Surgical Training (IST) pilot is delivery of better quality of early years surgical training. However, the quality of the trainee-trainer relationship can positively or negatively impact trainees' experiences of the specialty. Trust is a key determinant of the relationship, which is influenced by trainers' level of risk aversion and trainees' motivation. Game theory provides a framework to understand cooperation amongst rational 'players'. This study explores how trainee-trainer relationships impact trainees' experiences through the IST curricular reform. Methods: Using a qualitative case study approach, data were obtained from interviews with core surgical trainees across Scotland. Data coding and inductive thematic analysis were undertaken. Results: Forty-six trainees participated. Trainees and trainers regularly interacting in clinical activities demonstrated growing levels of trust, aided by: specialty rotations of 6 months or more duration, working at junior registrar level with structured weekly clinical activities and direct consultant supervision, individual goal-setting and regular progress check, and meaningful and timely feedback. Cooperative relationships led to individual fulfilment, growth, and trainee autonomy. Factors hindering development of trust included: temporal and/or geographical distance between trainee-trainer, poor communication and understanding of expectations and training needs, and lack of interest and enthusiasm from either party. Conclusion: Cohesive trainee-trainer relationships demonstrated cooperative equilibrium; both trainees and trainers met each other's expectations and positively impacted on trainees' experiences. On the contrary, 'players' in relationships deficient in trust achieved the minimum to ensure trainee progression. Addressing factors fostering a cooperative trainee-trainer relationship positively impacts trainees' experiences.